Model Pembelajaran Pendidikan Jasmani Berbasis Kompetensi - Agus Sisworo Dwi Marhaendro (Jurnal Pendidikan Jasmani Indonesia, 2010)
This paper aims to try to peel about learning modet that can achieve the objectives of the physical education as a whole, starting from physical development, movement, mental to social development. lt is based, first by the fact neglect of physical education in this country, starting from unmet needs physical education teacher until the fulfillment of the need for the facilities and the infrastructure. Second, the schools charge more dominant in the school of knowledge ratherthan everyday knowledge. Therefore if is necessa ry to use physical education model that can meet the load action knowledge by utilizing existing infrastructure. From the idea that school is life itself, then the model of physicat education should reflect on everyday life. Lifeifself is a competition for humans, therefore it can be created based on the physicaleducation modelof competition, namely by applying the competition of sports in the school environment. Through these competitions, students are expected to be directly involved in several aspecfs related to sport competition, sports competition proper in the general population. Modelbased physical education competition comes from studenfs, by students and for students. Sfudenfs as learners have the freedom to choose their respective roles, as in real life, where people must determine their respective roles. Learners should be able to learn by their self , do not depend on teachers (self-directing learning) through the experiences and actions. Keywords: everyday knowledge, self-directed learning, physical education